Interstitial lung diseases with concomitant lung cancer: a data mining approach revealing a complex condition with gender- and immune-associated specific implications - Perrotta, Fabio; Lacedonia, Donato; D’Agnano, Vito; Bianco, Andrea; Scioscia, Giulia; Tondo, Pasquale; Foschino Barbaro, Maria Pia; Mariani, Francesca; Lettieri, Sara; Del Frate, Lucia; Mancinelli, Silvia; Piloni, Davide; et al. (Frontiers in Oncology, 2024)
BackgroundInterstitial lung diseases (ILDs) comprise a family of heterogeneous entities, primarily characterised by chronic scarring of the lung parenchyma. Among ILDs, idiopathic pulmonary fibrosis (IPF) is the most common idiopathic interstitial pneumonitis, associated with progressive functional decline leading to respiratory failure, a high symptom burden, and mortality. Notably, the incidence of lung cancer (LC) in patients already affected by ILDs—mainly IPF—is significantly higher than in the general population. Moreover, these cases are often neglected and deprived of active oncologic treatments.MethodsWe here aim to identify variables predictive of outcome (mortality) in a multicentre retrospective cohort of ILD associated with lung cancer, collected from 2018 to the end of 2023. Overall, 73 cases were identified, and exhaustive clinicopathologic data were available for 55 patients. Among them, 42 had IPF. The entire dataset was then analysed by using the JMP partition algorithm (JMP-Statistical Discoveries, from SAS), which can choose the optimum splits from many possible trees, making it a powerful modelling and data discovery tool.ResultsThe average age at lung cancer diagnosis was 71.4 years, whereas the average age at IPF diagnosis was 69.5 years. The average Charlson Comorbidity Index was 4.6. Female patients constituted 28.3% (15) of the evaluated cases. The most frequent tumour histotype was adenocarcinoma (45.2%), and in more than 60% of the cases (67.9%), cancer was diagnosed at an early stage (TNM I–II–IIIA). A significant gender difference emerges regarding the overall patient survival, and quite unexpectedly, surgical approach to IPF-associated LC and the detection of serum autoantibodies are among the strongest outcome predictors.ConclusionsThe analysis performed is descriptive and successfully identifies key features of this specific and rare cancer population. IPF-associated LC emerges as a unique malignant disease defined by specific gender and histopathologic clinical and molecular parameters, which might benefit from active treatments.